Perspektif Fikih Muamalah Terhadap Sistem Penjualan Pertamax Oleh Pertamina ke Pertashop - Daga Suryadi; FauziYati Yati (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
The research was motivated by a mismatch in the number of orders for Pertamax type fuel oil ordered with those arriving at Pertashop. There is a shortage of fuel oil or losses. For further research, this research uses field research methods. The data collection techniques use observation, interviews and documentation. Then the collected data is processed and written using qualitative analysis. Based on the research results, the findings in this research are that the implementation of the sale and purchase of Pertamax fuel oil between Pertamina and Pertashop in Nagari Maek uses a DO (delivery order) system through the My Pertamina application. If the DO is successful, then Pertashop pays via ATM or mobile banking or bank teller which will come after 2 or 3 days. After the fuel oil arrives at Pertashop, it is transferred to the Pertashop tank. Next, the Pertashop owner signs the purchase note. Furthermore, the factor causing fuel oil to decrease when it is unloaded at Pertashop is the weather. Then, a muamalah fiqh review of the sale and purchase of Pertamax fuel oil between Pertamina and Pertashop in Nagari Maek can be carried out. This sale and purchase does not contain any gharar elements in it, but rather natural factors which cause the fuel oil to decrease when checked in the Pertashop tank. Apart from that, the losses of the Pertamax type fuel oil are still within tolerance as a fuel oil characteristic.